Ergodicity for neutral type SDEs with infinite length of memory. Issue 9 (24th June 2020) - Bao, Jianhai; Wang, Feng‐Yu; Yuan, Chenggui
Abstract: In this paper, the weak Harris theorem developed in [18] is illustrated by using a straightforward Wasserstein coupling, which implies the exponential ergodicity of the functional solutions to a range of neutral type SDEs with infinite length of memory. A concrete example is presented to illustrate the main result.